2004
DOI: 10.1007/s00701-004-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Occipital condyle fractures: a hidden nosologic an entity. An experience with 10 cases

Abstract: OCFs are actually not rare, rather they are often overlooked. In cases of high-energy trauma of the cervical spine, the diagnostic suspicion should be kept in mind.High-resolution CT scan with slice at 1-2 mm of the CCJ is the key radiological examination in the diagnosis of this lesion. Conservative treatment using a hard collar is sufficient to obtain sound fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 1 publication
1
19
0
4
Order By: Relevance
“…Capuano et al [6] in a review of literature found 11 reported cases between 1817 and 1974 and 225 cases up to 1999. High resolution reconstructed CT imaging is the gold standard technique in diagnosis and also provides precise data on degree of displacement of fractured bone [7].…”
Section: Discussionmentioning
confidence: 99%
“…Capuano et al [6] in a review of literature found 11 reported cases between 1817 and 1974 and 225 cases up to 1999. High resolution reconstructed CT imaging is the gold standard technique in diagnosis and also provides precise data on degree of displacement of fractured bone [7].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of patients with an OCF is highly variable, ranging from mild neck pain to severe neurological sign such as quadriplegia 6) . Diagnosing associated brainstem and J Kor Neurotraumatol Soc vascular lesions are rare in high-energy fatal cases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnosis of OCF can be delayed even in an alert patient, where the occipito-cervical pain on the side of the OCF is often masked by the "non-specific" neck pain associated with the head and neck trauma. Moreover, there is a difficulty in diagnosing intubated patients due to the inability of complaining of any clinical symptoms 6,19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Alle Patienten wurden konservativ behandelt, bei allen Patienten trat eine knöcherne Heilung ein. Die Autoren schlussfolgern, dass es sich tatsäch-lich nicht um eine selten vorkommende, sondern vielmehr um eine selten erkannte Verletzung handelt, auf die im Rahmen der CT-Diagnostik besonders geachtet werden müsse [10].…”
Section: Kondylenfrakturunclassified